Model of Customer Value Approach for Improving Satisfaction of the Hospital Patients - Alimudin, Arasy (Economic and Bussiness Faculty, Dr Soetomo University, 2017)
Health service is highly demanded by public therefore it need to be balanced with the development of health care providers. The development of health care provider plays important role in determining service satisfaction. Hospitals which are unable to provide excellent quality service will loss customer value trust which lead to customer dissatisfaction.The present study aims to examineimpact of service quality and confidence in the value of patientinrelated to patient satisfaction. The present study utilizes 100 patients of inpatient hospital clinic in Surabaya as respondents in which the daya is analyzed by using SEM analysis technique. The result shows that direct effect of service quality on satisfaction is smaller than the indirect effect of service quality on customer satisfaction through value. Furthermore, direct effect of trust on satisfaction is smaller than indirect effect of trust on satisfaction through customer value.